2021
DOI: 10.1021/acs.analchem.0c05480
|View full text |Cite
|
Sign up to set email alerts
|

A Caffeic Acid Matrix Improves In Situ Detection and Imaging of Proteins with High Molecular Weight Close to 200,000 Da in Tissues by Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry Imaging

Abstract: To our knowledge, this was the first study in which caffeic acid (CA) was successfully evaluated as a matrix to enhance the in situ detection and imaging of endogenous proteins in three biological tissue sections (i.e., a rat brain and Capparis masaikai and germinating soybean seeds) by matrix-assisted laser desorption/ ionization mass spectrometry imaging (MALDI-MSI). Our results show several properties of CA, including strong ultraviolet absorption, a super-wide MS detection mass range close to 200,000 Da, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 56 publications
0
53
0
Order By: Relevance
“…Then in 2010, MALDI imaging exceeding 50 kDa was accomplished using a high mass detector [ 82 ]. More recently, with the application of a caffeic acid matrix, proteins with high molecular weight close to 200 kDa was successfully imaged by MALDI-MSI [ 83 ].…”
Section: Main Textmentioning
confidence: 99%
“…Then in 2010, MALDI imaging exceeding 50 kDa was accomplished using a high mass detector [ 82 ]. More recently, with the application of a caffeic acid matrix, proteins with high molecular weight close to 200 kDa was successfully imaged by MALDI-MSI [ 83 ].…”
Section: Main Textmentioning
confidence: 99%
“…Modern MS instrumentation has reached the sensitivity for spatially resolved top-down proteomics suitable for imaging experiments (17,18). Matrix-assisted laser desorption/ionization (MALDI) is widely used for protein imaging (19,20) because of the broad mass range of proteome sampling (21)(22)(23). However, MALDI predominantly generates singly charged ions, which gives limited fragment information for direct top-down identification of intact proteins (24).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown imaging of proteins up to 200 kDa. 13 , 14 MSI of trypsinized proteins can therefore—at least theoretically—increase the coverage of the proteome beyond this sensitivity limit. Moreover, the on-tissue digestion approach allows better integration of MSI data with liquid chromatography-tandem mass spectrometry (LC-MS/MS) of the same or an adjacent tissue section to enable the identification of the observed local peptide signals, especially when using high-mass resolution MSI instrumentation.…”
Section: Introductionmentioning
confidence: 99%
“…Intact proteins can be detected by MSI; however, their detection is limited by low ionization efficiency that limits sensitivity in the high mass range of the instrumentation. Recent studies have shown imaging of proteins up to 200 kDa. , MSI of trypsinized proteins can thereforeat least theoreticallyincrease the coverage of the proteome beyond this sensitivity limit. Moreover, the on-tissue digestion approach allows better integration of MSI data with liquid chromatography-tandem mass spectrometry (LC-MS/MS) of the same or an adjacent tissue section to enable the identification of the observed local peptide signals, especially when using high-mass resolution MSI instrumentation. , However, these high-mass resolution MSI methods are limited by a long acquisition time and consequently suffer from a low throughput.…”
Section: Introductionmentioning
confidence: 99%